2003
DOI: 10.1590/s0102-311x2003000300013
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between dental status, food selection, nutrient intake, nutritional status, and body mass index in older people

Abstract: This paper reviewed the findings from a national survey in Great Britain which assessed whether dental status affected older people's food selection, nutrient intake, and nutritional status. The survey analyzed national random samples of free-living and institution subjects for dental examination, interview, and four-day food diary as well as blood and urine tests In the free-living sample, intakes of non-starch polysaccharides, protein, calcium, non-heme iron, niacin, and vitamin C were significantly lower in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
172
6
33

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(232 citation statements)
references
References 10 publications
21
172
6
33
Order By: Relevance
“…Desta forma, a odontologia desempenha papel fundamental, pois, a manutenção da saúde bucal é essencial para uma boa alimentação e nutrição destes sujeitos (MARCENES et al, 2003) . Idosos com perda de todos os elementos dentais são os que mais apresentam dificuldades para se alimentar, principalmente quando a prótese total utilizada não apresenta boas condições, optando por uma alimentação macia e fácil de mastigar, a qual apresenta geralmente baixo teor nutricional (MARTINS, BARRETO, PORDEUS, 2008).…”
Section: R Bras CI Saúde 15(2):183-190 2011unclassified
See 1 more Smart Citation
“…Desta forma, a odontologia desempenha papel fundamental, pois, a manutenção da saúde bucal é essencial para uma boa alimentação e nutrição destes sujeitos (MARCENES et al, 2003) . Idosos com perda de todos os elementos dentais são os que mais apresentam dificuldades para se alimentar, principalmente quando a prótese total utilizada não apresenta boas condições, optando por uma alimentação macia e fácil de mastigar, a qual apresenta geralmente baixo teor nutricional (MARTINS, BARRETO, PORDEUS, 2008).…”
Section: R Bras CI Saúde 15(2):183-190 2011unclassified
“…O quadro epidemiológico e a ausência de programas voltados para a população geriátrica brasileira caracterizam a péssima condição de saúde bucal encontrada nesse grupo (SILVA, SOUZA, WADA, 2005, SAINTRAIN, VIEIRA, 2008, MARCENES et al, 2003. É muito importante a obtenção de dados epidemiológicos, pois esses quantificam as condições de saúde bucal dos indivíduos, além de serem usados no planejamento, organização e monitoramento dos serviços de saúde prestados (FERNANDES et al, 1997, SILVA, CASTELLANOS-FERNANDES, 2001).…”
Section: R Bras CI Saúde 15(2):183-190 2011unclassified
“…However, most authors considered the worsening nutritional state as the low weight according to the Body Mass Index (BMI) [16][17][18][19] . To date, only one study has been published that has used a measurement capable of identifying nutritional risk, such as the Mini Nutritional Assessment (MNA) 14 , with noninstitutionalized elderly Brazilians and demonstrated an association between the number of remaining teeth and nutritional status.…”
Section: Introductionmentioning
confidence: 99%
“…Observations from a previous study (9) revealed that edentulous participants had a lower intake of vegetables, lower intake of fibre and carotene, and higher intake of cholesterol, saturated fat, and calories than participants with 25 or more teeth. The importance of teeth and their association with a healthy diet rich in fruit and vegetables, satisfactory nutritional status, and acceptable body-mass index has also been highlighted (28).…”
Section: Discussionmentioning
confidence: 99%